PEMANFAATAN SARI TEBU (Saccharum Oficinarum) DAN LAMA FERMENTASI KACANG TUNGGAK TERHADAP KUALITAS KECAP MANIS KACANG TUNGGAK (Vigna Unguiculata) - Ernasari Ernasari; Patang Patang; Kadirman Kadirman (Universitas Negeri Makassar, 2018)
The purpose of this study to determine the effect utilization of cane sari concentration and fermentation long to the quality of cowpea sweet soy sauce that produced. This research is an experimen research with a complete randomized design of factorial pattern (factorial RAL) consisting of two factors, namely the of juice sugar cane concentration 3 treatment, namely: 100 ml, 200 ml, and 300 ml. and fermentation long that is : 3 days, 5 days and 7 days. Research variables observed were protein content, viscosity and sucrose sugar content. The analytical technique used in this study is the of analysis variety .The results showed the best treatment on the addition of cane sari for organoleptic test (taste, color and aroma) and proximate analysis for viscosity and sugar levels sucrose on addition of concentration 300 ml , for levels protein the best treatment on addition concentration 100 ml. whereas The best treatments on fermentation long for organoleptic test included (taste, color and aroma) and proximate analysis such as protein content, viscosity and sucrose sugar content with 3 days fermentation long.